2009
DOI: 10.1007/s11051-009-9833-5
|View full text |Cite
|
Sign up to set email alerts
|

Influence of synthesis method on structural and magnetic properties of cobalt ferrite nanoparticles

Abstract: The Co-ferrite nanoparticles having a relatively uniform size distribution around 8 nm were synthesized by three different methods. A simple coprecipitation from aqueous solutions and a coprecipitation in an environment of microemulsions are low temperature methods (50°C), whereas a thermal decomposition of organo-metallic complexes was performed at elevated temperature of 290°C. The X-ray diffractometry (XRD) showed spinel structure, and the high-resolution transmission electron microscopy (HRTEM) a good crys… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
31
0
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 129 publications
(37 citation statements)
references
References 34 publications
5
31
0
1
Order By: Relevance
“…Co-precipitation 800 [8] Co-precipitation 850 [30] Co-precipitation in reverse microemulsion 700 [8] Thermal decomposition 1900 [8] Combustion 2002 [30] Sol/Gel (citrate method) 2000 This work Table 3 …”
Section: Compositionmentioning
confidence: 99%
See 1 more Smart Citation
“…Co-precipitation 800 [8] Co-precipitation 850 [30] Co-precipitation in reverse microemulsion 700 [8] Thermal decomposition 1900 [8] Combustion 2002 [30] Sol/Gel (citrate method) 2000 This work Table 3 …”
Section: Compositionmentioning
confidence: 99%
“…Several preparation techniques have been used for the synthesis of ferrites nano-particles, which exhibit novel properties. Gyergyek et al [8] has reported the synthesis method effect on particles sizes and magnetic properties in Cobalt ferrite using three different techniques: co-precipitation, microemulsion method and thermal decomposition. The results show a significant variation of saturation magnetization and coercitivity.…”
mentioning
confidence: 99%
“…The syntheses that do exist are often limited to a few selected types of nanoparticles and only use a few different synthetic protocols, despite the fact that the syntheses used may not be the best method to use to make nanoparticles with specific properties [1,2]. It has been shown that different syntheses can lead to vastly different properties, even if the nanoparticles appear the same or very similar in terms of size and shape [1,[3][4][5].…”
Section: Introductionmentioning
confidence: 99%
“…The extensive research on CoFe 2 O 4 thin films has been carried out because of their incredible applications such as gas sensor [5], fabrication of higher frequency device etc., [6][7][8][9]. Recently, cobalt ferrite thin films, substituted cobalt ferrite, and their composites have been used as potential materials for gas sensing applications [10][11][12][13].…”
Section: Introductionmentioning
confidence: 99%